Development and application of flood impact maps under climate change scenarios: A case study of the Yilan area of Taiwan - Hsiao, Yi-Hua; Chen, Chun-Che; Chao, Yi-Chiung; Li, Hsih-Chi; Ho, Ching-Hsien; Hsu, Chih-Tsung; Yeh, Keh-Chia (Frontiers in Environmental Science, 2022)
Flooding is the main disaster type in Taiwan and is usually caused by typhoons and heavy rainfall. To understand the flood impacts in Taiwan caused by increasing rainfall due to global warming, this study adopts a high-resolution atmospheric model (HiRAM) under the representative concentration pathway (RCP) 8.5 scenario to project future changes in flood impact. For the flood simulation, the SOBEK flood model was used to determine the maximum accumulated flooding depth and flood probability in the two periods of the present and the middle of the 21st century. Yilan County, one of the most flood-prone areas in Taiwan, was chosen as a demonstration case for the development of flood impact maps. According to the results of flood map application, flooded areas were predicted to increase in the middle period of the 21st century due to increasing rainfall, especially in paddy fields, maricultural farms, and stock farms. From the base period to the middle of the 21st century, the area of flooding impacts was projected to increase from 24% to 40% in paddy fields, from 9% to 15% in maricultural farms, and from less than 1% to 9% in stock farms. These results show that the development of flood maps can help elucidate the actual impacts of climate change in Taiwan and serve as a scientific basis for adaptation actions.